Environmental Factors and Efficacy of Castor Seed Influencing Aedes aegypti Larval Presence - Chahaya, Indra; Tumanggor, Winni R. E.; Arde, Lanova Dwi; Khairunnisa; Shadrina, Najwa; Purba, Lyra Caroline D (Jurnal Kesehatan Masyarakat, 2025)
Dengue hemorrhagic fever (DHF) is a major global health challenge, especially in areas endemic to Aedes aegypti mosquito. This study analyzes the environmental factors influencing larval presence and investigates the effectiveness of natural larvicides from castor seed (Ricinus communis) in controlling Ae. aegypti mosquito larvae. Using a cross-sectional survey of households by purposive sampling between those located near and far from public places and a quasi-experimental study compared households in the intervention group (using castor seed powder larvicide) with those in the comparison group (not using castor seed powder larvicide) were conducted in Medan Amplas District, Medan City. The study found that location significantly impacts mosquito larvae (p = 0.045, OR 3.26, 95% CI), with households near public places at higher risk. Applying castor seed-based natural larvicide at 100 mg/L of water (p = 0.0001, OR 37.76, 95% CI 17.9-79.2) significantly reduced larvae, with a 37.76-fold higher likelihood of larval absence than the comparison group. Notably, the use of castor seed powder demonstrated exceptional effectiveness in reducing the presence of Ae. aegypti mosquito larvae. These findings highlight the potential of castor seed natural larvicides as a sustainable and environmentally friendly alternative to chemical larvicides, particularly for households near public places.